2006
DOI: 10.1590/s0100-879x2006000200014
|View full text |Cite
|
Sign up to set email alerts
|

<a name="home"></a>Activation of neural cholecystokinin-1 receptors induces relaxation of the isolated rat duodenum which is reduced by nitric oxide synthase inhibitors

Abstract: Cholecystokinin (CCK) influences gastrointestinal motility, by acting on central and peripheral receptors. The aim of the present study was to determine whether CCK has any effect on isolated duodenum longitudinal muscle activity and to characterize the mechanisms involved. Isolated segments of the rat proximal duodenum were mounted for the recording of isometric contractions of longitudinal muscle in the presence of atropine and guanethidine. CCK-8S (EC 50 : 39; 95% CI: 4.1-152 nM) and cerulein (EC 50 : 58; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The result of the present study are consistent with the research of Martins et al, which indicated that endogenous CCK inhibited the spontaneous contraction of duodenal longitudinal muscle via V 1 receptors on myenteric neurons [5]. The CCK 1 receptors were located on vagal afferent neurons [22], myenteric neurons, and interstitial cell of Cajal [11].…”
Section: Discussionsupporting
confidence: 93%
“…The result of the present study are consistent with the research of Martins et al, which indicated that endogenous CCK inhibited the spontaneous contraction of duodenal longitudinal muscle via V 1 receptors on myenteric neurons [5]. The CCK 1 receptors were located on vagal afferent neurons [22], myenteric neurons, and interstitial cell of Cajal [11].…”
Section: Discussionsupporting
confidence: 93%
“…There is rather no doubt that CCK stimulates phasic contractions in the small intestine (Bueno and Praddaude 1979;Giuliani et al 1990;Mukhopadhyay et al 1977;Romaƒski 2002) although there are some reports showing that duodenum did not respond significantly to CCK administration especially when the studies were performed in fasted animals (Wingate et al 1978). Its action can be also inhibitory as studied on isolated rat duodenum (Martins et al 2006). The effects of CCK on tonic contractions within the gastrointestinal tract have not been extensively examined and the effect of CCK on the tonic component in the small bowel in sheep is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were reported for cerulein (Bertaccini et al, 1968;Ormas et al, 1984;Niederau and Karaus, 1991;Romański, 2004). Other reports indicate that the The explanations for Table 1 values expresseding/s/min; 0-10 -one-minute consecutive periods; 0 -control period, 1-10 -period safter hormone administration; dose of the hormone expressed in ng/kg; duration of hormone administration expressed in seconds (s); the values of three previous control periods, insignificantly different from period 0, are not shown; statistical significances: a P < 0.05; b P < 0.01; c P < 0.001 vs. relevant value of period 0; other explanations see the text The explanation see Table 1 effect of CCK action on duodenal motility can be inhibitory or no effect can be observed while some authors observed a simultaneous stimulatory effect in the jejunum (Fleckenstein and Öigaard, 1977;Bueno and Praddaude, 1979;Giralt and Vergara, 2000;Martins et al, 2006). This confirms the view that the character of CCK action can be different in the various small intestinal segments.…”
Section: Discussionmentioning
confidence: 94%
“…Pretreatment with CCK receptor antagonist reverses this action (Niederau and Karaus, 1991;Xu et al, 1998). However, the opposite and dual effects of CCK-OP and its amphibian analogue, cerulein, have been reported (Giuliani et al, 1990;Martins et al, 2006). In sheep, CCK peptides also inhibit the arrival of the MMC in the upper small intestine, but their effect on intestinal motility has not been fully elucidated so far in spite of several studies performed (Bueno and Praddaude, 1979;Cottrell and Iggo, 1984;Ormas et al, 1984;Onaga et al, 1997;Romański, 2004Romański, , 2007b.…”
mentioning
confidence: 99%